Associação entre o hábito alimentar na gestação e peso ao nascer em crianças nascidas a termo em Itaqui/RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
To analyze the association between dietary habits during the gestational period and birth weight. Methods: Cross-sectional epidemiological and quantitative study of the observational type carried out for convenience. A Food Frequency Questionnaire was applied for the evaluation of food consumption, and the weight of the newborn was classified according to WHO. The analyzes were performed in SPSS version 20.0. The categorical variables were analyzed by the chi-square test and the analysis of variance (ANOVA) was used to verify the mean birth weight according to food consumption categories. Results: The sample consisted of 47 postpartum women. The findings of the present study show that 40.4% of the women presented eutrophy and 38.3% pre-gestational overweight. Weight adequacy was present in 76.6% of the born and 12.8% presented low weight. Of the women, 48.9% consumed fried / fried foods once a month, 23.4% once consumed soft drinks and artificial juices and 34% consumed sweets and sugars once a day. About 80% of the sample consume cereal twice a day. Fruits, vegetables and vegetables consumption was also frequent. Therefore, there was no relationship between eating habits during gestation and birth weight. Conclusion: There was no significant association between dietary habits and birth weight in the group of puerperal women evaluated.
Keywords: Gravidez; Consumo alimentar; Peso ao nascer; Pregnancy; Food intake; Birth weight; CNPQ::CIENCIAS DA SAUDE